Epidemiological Characteristics of Strongyloidiasis in Inhabitants of Indigenous Communities in Borneo Island, Malaysia - Romano, Ngui; Noor Amira, Abdul Halim; Yamuna, Rajoo; Yvonne Ai, Lian Lim; Stephen, Ambu; Komalaveni, Rajoo; Tey, Siew Chang; Lu, Chan Woon; Rohela, Mahmud (Korean Society for Parasitology, 2016)
Epidemiological study on strongyloidiasis in humans is currently lacking in Malaysia. Thus, a cross-sectional study was carried out to determine the prevalence of Strongyloides stercoralis infection among the inhabitants of longhouse indigenous communities in Sarawak. A single stool and blood sample were collected from each participant and subjected to microscopy, serological and molecular techniques. Five species of intestinal parasites were identified by stool microscopy. None of the stool samples were positive for S. stercoralis. However, 11% of 236 serum samples were seropositive for strongyloidiasis. Further confirmation using molecular technique on stool samples of the seropositive individuals successfully amplified 5 samples, suggesting current active infections. The prevalence was significantly higher in adult males and tended to increase with age. S. stercoralis should no longer be neglected in any intestinal parasitic survey. Combination of more than 1 diagnostic technique is necessary to increase the likelihood of estimating the ‘true’ prevalence of S. stercoralis.